2017
DOI: 10.22606/ijper.2017.11003
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Spectroscopy (EIS) Characterization of Reformate-operated High Temperature PEM Fuel Cell Stack

Abstract: This paper presents an experimental characterization of a high temperature proton exchange membrane fuel cell (HT-PEMFC) short stack carried out by means of impedance spectroscopy. Selected operating parameters; temperature, stoichiometry and reactant compositions were varied to investigate their effects on a reformate-operated stack. Polarization curves were also recorded to complement the impedance analysis of the researched phenomena. An equivalent circuit model was used to estimate the different resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The diameter of the impedance arc is the sum of the charge transfer and mass transfer resistance. The reduction in the arc diameter at higher temperatures indicates that there is a slight improvement in mass transport and high frequency charge transfer [ 49 ]. According to Su et al [ 50 ], an increase in temperature enhances the cell performance due to the increase in the mass transfer rate, and a lower cell resistance, as confirmed in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of the impedance arc is the sum of the charge transfer and mass transfer resistance. The reduction in the arc diameter at higher temperatures indicates that there is a slight improvement in mass transport and high frequency charge transfer [ 49 ]. According to Su et al [ 50 ], an increase in temperature enhances the cell performance due to the increase in the mass transfer rate, and a lower cell resistance, as confirmed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…According to Su et al [ 50 ], an increase in temperature enhances the cell performance due to the increase in the mass transfer rate, and a lower cell resistance, as confirmed in this work. Furthermore, the overall performance enhancement with increasing temperatures (polarization curves) can be attributed to the decrease in ohmic resistance and the improvement in mass transport and high frequency charge transfer observed in the EIS data [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shortly after, the load current was increased stepwise up to 6.35 A. The stoichiometry factor is based on the ratio between the available gas at the inlet and the required gas necessary for the reaction [32].…”
Section: Methodsmentioning
confidence: 99%
“…Note that this value is slightly higher than the one used in the experimental test and voltage values calculated by the model may slightly underestimate real values. However, in an experimental work performed in a similar short HT-PEMFC stack, it was found that once hydrogen starvation is avoided at around an anode stoichiometric ratio of 1.3, further increase in λ anode does not improve the fuel cell stack performance [41].…”
Section: System Modelingmentioning
confidence: 98%